Metallic elements combine with herbal compounds upload in microneedles to promote wound healing: a review - Tang, Xiao; Li, Li; You, Gehang; Li, Xinyi; Kang, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Wound healing is a dynamic and complex restorative process, and traditional dressings reduce their therapeutic effectiveness due to the accumulation of drugs in the cuticle. As a novel drug delivery system, microneedles (MNs) can overcome the defect and deliver drugs to the deeper layers of the skin. As the core of the microneedle system, loaded drugs exert a significant influence on the therapeutic efficacy of MNs. Metallic elements and herbal compounds have been widely used in wound treatment for their ability to accelerate the healing process. Metallic elements primarily serve as antimicrobial agents and facilitate the enhancement of cell proliferation. Whereas various herbal compounds act on different targets in the inflammatory, proliferative, and remodeling phases of wound healing. The interaction between the two drugs forms nanoparticles (NPs) and metal-organic frameworks (MOFs), reducing the toxicity of the metallic elements and increasing the therapeutic effect. This article summarizes recent trends in the development of MNs made of metallic elements and herbal compounds for wound healing, describes their advantages in wound treatment, and provides a reference for the development of future MNs.